Utilization of Traditional Games in Physical Education Learning for Elementary School Students’ Motor Reading - Udzma, Septira Nafa’atul; Ulya, Azida Gina; Husna, Azizah Nailul; Pathurrahman, Pathurrahman (Yayasan Insan Mulia Bima, 2025)
This study aims to describe the use of traditional games in Physical Education, Sports, and Health (PJOK) learning as an effort to develop elementary school students' motor skills. Traditional games are considered relevant to the characteristics of elementary school students who tend to be active and enjoy playing, and are in line with the objectives of PJOK learning which not only emphasize physical aspects, but also social and emotional aspects. This study uses a qualitative descriptive approach with data collection techniques in the form of observation, interviews, and documentation. The subjects of the study were PJOK teachers and students at an elementary school. The results of the study showed that traditional games such as rope jumping, hide and seek, gobak sodor, and engklek. can improve students' gross motor skills, such as balance, agility, and coordination of movement. In addition, this activity also fosters cooperation, sportsmanship, and a spirit of togetherness among students. In conclusion, the use of traditional games in PJOK learning is very effective in developing elementary school students' motor aspects in a fun and contextual way. Therefore, teachers suggest integrating traditional games as an alternative active learning strategy that is appropriate to child development.